"She's Nobody's Child/the Law Can't Touch Her at All": Seeking to Bring Dignity to Legal Proceedings Involving Juveniles. (30th January 2018) - Perlin, Michael L.; Lynch, Alison J.
Abstract : Inquiries into a range of issues involving juveniles in the psychiatric hospitalization and criminal trial process reveal that, regularly, juveniles are subject to shame and humiliation in all aspects of the legal system that relate to arrest, trial, conviction, and institutionalization, shame and humiliation that are often exacerbated in cases involving racial minorities and those who are economically impoverished. We contextualize them into the juvenile justice system, and look specifically at how this is reflected in the case law. We then consider these findings through the filters of therapeutic jurisprudence and international human rights laws, concluding that these approaches best remediate the current state of affairs and infuse this system with badly‐needed dignity. Key points for the Family Court Community: We discuss why and how all relevant aspects of the legal system shame and humiliate juveniles, and deprive juveniles of dignity, whether in the civil commitment system, the criminal justice system, or the correctional system. We explain why this shame and humiliation disproportionately affects racial minorities and those who are economically impoverished. We discuss why the application of international human rights law and therapeutic jurisprudence can best remediate this shame and humiliation.